2018
DOI: 10.1002/suco.201700237
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of crack width calculation methods for RC ties

Abstract: This paper theoretically and experimentally investigates the semi‐empirical formulas recommended by Eurocode 2 (EC2), fib Model Code 2010 (MC2010), and Eurocode 2 with the German National Annex (DIN) for calculating crack widths in reinforced concrete. It is shown that the formulas can be derived from the principles for the idealized behavior of RC ties. However, instead of explicitly solving the resulting differential equations, the use of simplifications leads to inconsistent formulas. An experimental study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 16 publications
1
31
1
1
Order By: Relevance
“…12. Comparison of crack widths predicted (in specimens with lengths similar to crack spacing predicted in Table 2) with crack widths reported in F12:2 experiments: (a) CEOS.fr (2016); and (b) Tan et al (2018a).…”
Section: Comparison With Nonaxisymmetric Rc Tiesmentioning
confidence: 85%
See 3 more Smart Citations
“…12. Comparison of crack widths predicted (in specimens with lengths similar to crack spacing predicted in Table 2) with crack widths reported in F12:2 experiments: (a) CEOS.fr (2016); and (b) Tan et al (2018a).…”
Section: Comparison With Nonaxisymmetric Rc Tiesmentioning
confidence: 85%
“…Nevertheless, the maximum crack spacing predictions were conservative, and the crack widths predicted show relatively good agreement with the maximum crack widths measured. Tan et al (2018a) conducted experiments on eight quadratic RC ties identified as X-ϕ-c, where X represents the loading regime the RC tie was exposed to, either at the crack formation stage (F) or the stabilized cracking stage (S), while ϕ and c represent the rebar diameter and cover respectively. The rebar diameter was either 20 or 32 mm, while the cover was either 40 or 90 mm.…”
Section: Comparison With Nonaxisymmetric Rc Tiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, it can be found various types of data to identify the crack width governing parameters. However, with the advancement of material and geometrical properties of concrete and reinforcement, the authors have selected two recent axial tensile experiments mentioned in (Tan et al, 2018;Tan et al,2019) and (Rimkus and Gribniak, 2017), to identify the crack spacing governing parameters. The selected experiments consist of the RC ties with multiple reinforcement bars, which are more similar to the RC members in practice.…”
Section: Introductionmentioning
confidence: 99%